(untitled) (Herald of the National Children’s Medical Center, 2025)
In recent years, many countries around the world have seen a rise in the incidence of bronchial asthma (BA), especially in economically developed nations, where the number of cases has tripled. Increasingly, BA is observed in combination with excess body weight in children, which leads to a more severe course of the disease, worsens quality of life, and requires a specialized approach to treatment.